Relationship Among Phenolic Contents, Seed Predation, and Physical Seed Traits in Mimosa bimucronata Plants - Kestring, Debora [UNESP]; Menezes, Luciana C. C. R. [UNESP]; Tomaz, Camila A. [UNESP]; Lima, Giuseppina Pace Pereira [UNESP]; Rossi, Marcelo N. (Springer, 2009)
Phenolic contents were compared between Mimosa bimucronata seeds from infested and non-infested fruits to assess induced defense response. By measuring leg length of the bruchid beetle Acanthoscelides schrankiae, we verified whether phenolic contents affected bruchid body size. In addition, the relationship between physical seed traits and phenolic contents was examined. Results showed that seeds from infested fruits had significantly greater phenolic contents than seeds from non-infested fruits, which suggested induced defense. Body size variation in A. schrankiae was marginally nonsignificant according to phenolic contents among plants (negative trend), indicating that phenols may interfere directly with bruchid performance. Seeds that were more irregularly shaped had significantly greater phenolic contents than those that were more uniform. Therefore, the most perfectly spherical seeds may be more vulnerable to seed predation, and our results suggest that the production of phenolic compounds was increased in infested fruits, which in turn may affect A. schrankiae development.
Keywords: Acanthoscelides schrankiae; Induced defense; Insect body size; Phenolic compounds; Physical seed traits; Seed predation